Democracy, risk, and community : technological hazards and the evolution of liberalism - Hiskes, Richard P., 1951- (Environmental ethics and science policy., 1998)
Explores the connection between technological risk and basic concepts of liberal political theory and practice. The author argues that modern risks are emergent and therefore not reducible to individual actors or events, and that risks challenge basic concepts of liberal political theory.